Urinary tract infections caused by anaerobic bacteria. Utility of anaerobic urine culture. (December 2022) - Legaria, M.C.; Barberis, C.; Famiglietti, A.; De Gregorio, S.; Stecher, D.; Rodriguez, C.H.; Vay, C.A.
Abstract: Urinary tract infections (UTIs) caused by anaerobic bacteria have scarcely been reported. Since anaerobic bacteria are commensals of the genitourinary tract, their presence in a urine sample adds ambiguity in making a definitive diagnosis of anaerobic UTI. It is well known that standard urine culture is the gold standard method for the detection, identification, and antimicrobial susceptibility testing of uropathogens. Nonetheless, both the difficulties in establishing them as pathogens and the scarcity of reported anaerobic UTI cases led to the discontinuation of routine urine culture under an anaerobic atmosphere (UCAA). On the other hand, it is important to emphasize that culture-independent methods, such as proteomics and molecular technics, may detect anaerobes directly on a urine sample. Anaerobes are not included in guidelines for the diagnosis and management of UTIs. At the same time, as fastidious uropathogens and antibiotic resistance become more common, accurate pathogen identification becomes even more important for effective UTI treatment. As a result, we conducted a review of the clinical context, pathogen antimicrobial susceptibility, and treatment of patients with anaerobic UTIs. Because UCAA is a contentious topic, we narrowed our search to cases with both negative standard urine culture and positive UCAA. Highlights: Urinary tract infections (UTIs) features caused by anaerobic bacteria are reviewed. Anaerobic bacteria are detected in both UTIs and urinary microbiota. Some fastidious pathogens require urine culture under anaerobic atmosphere (UCAA). Genomic, proteomic, and culturomic approaches were used. Multiple treatments were frequently required.